ROLES OF MANAGEMENT COMMITMENT in MAINTANING OCCUPANCY HEALTH AND SAFETY (OHS) DURING COVID- 19 PANDEMIC IN HIGHER EDUCATION INSTITUTION - Evan Pratama; Hasyim Hasyim; Mukhamad Abduh; Rina Anindita (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
Since Covid-19 has been declared as pandemic, many sectors are affected, including higher education. Accordingly, the good management commitment to handle the pandemic effect in an internal of an organization or higher education institutions is needed, especially to mitigate fatality risk, as they provide service for global sectors. This research is expected to provide information on right strategy and action for Higher Education Institution management to apply, and to provide positive managerial implication on organization management. The purpose of this research is to find out to what extent Active Commitment, Passive Commitment, Employee Awareness and OHS Compliance in Higher Education Institution. This is a survey research by conducting questionnaire with one-shot study. The data was obtained from 200 respondents, the employees of Higher Education Institution in Tangerang, Banten on Januari to April 2021. The analysis method in this research was using SEM with LISREL. The research shows several results: a) high Active Commitment would increase Employee Awareness on OHS; b) low Passive Commitment management would increase Employee Awareness on OHS; c) high Employee Awareness affects OHS Compliance; d) high Passive Commitment management affects Compliance on OHS.